Pre-service teachers’ emotion in teaching practicum - Yayu Heryatun; Tri Ilma Septiana (University of Kuningan, 2020)
This present study involved two novice pre-service teachers who had teaching practicum. It focused on their emotion during two-months teaching practicum. Their emotion dealt with personal geography as well as professional geography. The results revealed that pre-service teacher had emotional experience positively and negatively. The emotional experience that pre-service teachers had in personal geographies starting from nervous, anxious, scared, guilty, shame, self-doubt and being oppressed to being calm, being enthusiasm to teach, having self-confidence and having good rapport with school citizens. Meanwhile, in term of professional geographies, pre-service teachers’ emotions were various, ranging from how to adopt theory to practice, confused how to interpret mentor teachers’ feedback to being disciple, learning how to both design lesson plan and manage classroom, learning to dress well and keeping good relation to students, mentor teacher, supervisors, and school staffs. In addition, this study found the culture influence on pre-service teachers personally and professionally. The Indonesia culture to respect senior emerge during teaching practicum such different social status between student and teacher, tendency to underestimate the value of quality and achievement.